Concept of Li-Fi on Smart Communication between Vehicles and Traffic Signals - Mugunthan, S. R. (Journal of Ubiquitous Computing and Communication Technologies, 2020)
Communication is an essential thing for any work to be done on desired condition. There are several ways are there to communicate between a person to a machine. Switches are made as primary communication medium to do a specific task by a machine. The advancement of technologies introduced a remote switch for operation. The advancement is still continuing with voice recognition, hand gesture movement and mind reading models. Recently machine to machine communication was introduced to communicate their status between another machine or a system for implementing smart work on its own intelligence. The paper introduces a smart communication between vehicles to traffic signals and vehicle to vehicle using Li-Fi (Light Fidelity) technology for sharing necessary information to the nearby vehicle. The paper also describes the limitations and challenges in the Li-Fi technology for further communication improvement.